Understanding the social determinants of health among Indigenous Canadians: priorities for health promotion policies and actions - Fariba Kolahdooz; Forouz Nader; Kyoung J. Yi; Sangita Sharma (Taylor & Francis Group, 2015)
Background: Indigenous Canadians have a life expectancy 12 years lower than the national average and experience higher rates of preventable chronic diseases compared with non-Indigenous Canadians. Transgenerational trauma from past assimilation policies have affected the health of Indigenous populations. Objective: The purpose of this paper is to comprehensively examine the social determinants of health (SDH), in order to identify priorities for health promotion policies and actions. Design: We undertook a series of systematic reviews focusing on four major SDH (i.e. income, education, employment, and housing) among Indigenous peoples in Alberta, following the protocol Preferred Reporting Items for Systematic Reviews and Meta-Analysis-Equity. Results: We found that the four SDH disproportionately affect the health of Indigenous peoples. Our systematic review highlighted 1) limited information regarding relationships and interactions among income, personal and social circumstances, and health outcomes; 2) limited knowledge of factors contributing to current housing status and its impacts on health outcomes; and 3) the limited number of studies involving the barriers to, and opportunities for, education. Conclusions: These findings may help to inform efforts to promote health equity and improve health outcomes of Indigenous Canadians. However, there is still a great need for in-depth subgroup studies to understand SDH (e.g. age, Indigenous ethnicity, dwelling area, etc.) and intersectoral collaborations (e.g. community and various government departments) to reduce health disparities faced by Indigenous Canadians.